ROAD TRAFFIC ESTIMATION USING BLUETOOTH SENSORS - Monika N. BUGDOL; Marcin D. BUGDOL; Marcin GRZEGORZEK; Andrzej W. MITAS (Scientific Journal of Silesian University of Technology. Series Transport, 2017)
The Bluetooth standard is a low-cost, very popular communication protocol offering a wide range of applications in many fields. In this paper, a novel system for road traffic estimation using Bluetooth sensors has been presented. The system consists of three main modules: filtration, statistical analysis of historical, and traffic estimation and prediction. The filtration module is responsible for the classification of road users and detecting measurements that should be removed. Traffic estimation has been performed on the basis of the data collected by Bluetooth measuring devices and information on external conditions (e.g., temperature), all of which have been gathered in the city of Bielsko-Biala (Poland). The obtained results are very promising. The smallest average relative error between the number of cars estimated by the model and the actual traffic was less than 10%.